First-principles study the single-layer transition metal trihalide CrXSe3 (X = Sn, Ge, Si) as monolayer ferromagnetic semiconductor. (19th November 2019) - Shen, Zihan; Fan, Xiaoli; Yang, Danxi; Gong, Yuanhao; Ma, Shiguo; Guo, Nijing; Hu, Yan; Benassi, Enrico; Lau, Woonming
Abstract: Layered transition metal trihalides ABX3 are promising candidate materials for monolayer magnets. In this paper, we investigated single-layer CrXSe3 (X  =  Sn, Ge, Si) as monolayer ferromagnetic semiconductors (FMS). Firstly, our calculated interlayer binding energies and mechanical properties demonstrate the feasibility of obtaining the free-standing monolayer CrXSe3 from the layered van der Waals crystal CrXSe3 via mechanical exfoliating method. Plus, we find that the ferromagnetic (FM) super-exchange interaction dominates over the anti-ferromagnetic (AFM) direct-exchange interactions, making CrSnSe3 and CrGeSe3 monolayers FM with the magnetic moments of 6.0 µ B per unit cell. Particularly, the FM configurations of CrSnSe3 and CrGeSe3 monolayers become more stable under the increasing tensile strain, and CrSiSe3 converts to FM from AFM under biaxial tensile strain larger than 2%. Additionally, the three monolayers CrXSe3 are all semiconducting with energy band gaps of 0.76, 0.87 and 1.1 eV for X being Sn, Ge and Si, respectively. Our results suggest CrXSe3 as monolayer FMS hold promising potential in spintronics.